Adult Learning and Investment Practices of Persons with Disability in Informal Microfinance Groups in Uganda - Nuwagaba, Ephraim Lemmy; Garuzooka, John Francis; Bakeizimba, Edigald (The Center for Disability Studies and Services Brawijaya University, 2024)
Microfinance can be an effective strategy for poverty reduction among Persons with Disability. However, lack of investment and livelihood knowledge and skills and consumption tendencies may undermine this strategy. A qualitative case study that explored the investment practices of Persons with Disability in informal microfinance groups was conducted in Uganda. Findings revealed that despite barriers to learning and investment, Persons with Disability who had positive attitudes borrowed from informal microfinance groups and invested profitably. They learned from a wide range of sources in their community. The study concludes that despite barriers, Persons with Disability borrow and invest and that attitudes, knowledge and skills, severity of impairment and location, influence their investment choices. To enhance investment, it is recommended that barriers to adult learning and investment be removed through sensitisation and training, monitoring compliance with accessibility standards and policy reforms.